Chicken said, "Cluck!" - Grant, Judyann; Truesdell, Sue (New York : HarperCollins, 2008)
Chicken wants to help Earl and Pearl plant their pumpkins, but she only manages to get in the way, until grasshoppers invade the pumpkin patch and Chicken is the only one who can stop them.
"Shared reading, my first."
Wilson's Children, July 2009
School Library Journal starred, November 2008
Kirkus Starred, September 2008
Horn Book, April 2009
Christian Library, October 2009
Keywords: Chickens -- Juvenile fiction; Gardening -- Juvenile fiction; Grasshoppers -- Juvenile fiction; Chickens -- Fiction; Gardening -- Fiction; Grasshoppers -- Fiction; Chickens -- Fiction; Gardening -- Fiction; Grasshoppers -- Fiction; Readers (Elementary)